Adjusting Expectations: Hearing Abilities in a Population-Based Sample Using an SSQ Short Form. (July 2018) - von Gablenz, Petra; Otto-Sobotka, Fabian; Holube, Inga
The German short form of the Speech, Spatial, and Qualities of Hearing Scale (SSQ) was administered in a cross-sectional study based on stratified random samples complemented by audiometric tests and a general interview. Data from 1, 711 unaided adults aged 18 to 97 years were analyzed in order to determine a distribution of hearing abilities considered as normal and the main factors that impact self-assessments. An innovative mathematical approach was used to overcome the constraints of statistics based on the mean. Quantile regression analysis yielded a benchmark distribution of SSQ scores that might support audiologists in setting realistic SSQ score targets and estimated how the effect of auditory and nonauditory factors changes across the distribution of SSQ scores. Regression models showed significant effects for nonauditory factors on SSQ ratings when controlled for pure-tone hearing and interaural asymmetry. Self-reporting of hearing difficulties, when asked in general terms, was substantially related to SSQ ratings. This effect was observed in both high and low scoring participants and led to a considerable score decrease in all SSQ subscales. Gender, educational level, and self-reporting of health issues also were significantly related to SSQ ratings, but the corresponding effects were regularly unbalanced across the score distribution and particularly large at lower quantiles. The estimated effects of age, however, were mostly small in size, inconsistent regarding the direction, and failed significance for all SSQ items. Overall, the results suggest that nonauditory factors and cumulative effects must be considered when evaluating rehabilitative interventions against an ideal outcome.